Paulo Freire's contributions to the intertwining of voices in critical English language teaching - Leite, Patrícia Mara de Carvalho Costa; Oliveira, Ana Cláudia Turcato de; Souza, Andréa Santana Silva e (Universidade Estadual de Campinas, 2022)
Supported by the assumptions of Critical Education and the understanding of Paulo Freire's work as one of the constitutive pillars of the Critical Literacies perspective, this article outlines considerations in favor of teaching and learning the English language for social justice and the construction of active citizenship. The main objective is to observe how intertwined they are, in order to indicate paths and foster inspiration for contextualized, meaningful, purposeful and critical English language teaching. The materials indicated here can contribute both to expanding the knowledge of school actors about the world, and to stimulating critical practices in the classroom.